1995
DOI: 10.1128/aac.39.3.672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cefodizime and ceftriaxone on phagocytic function in patients with severe infections

Abstract: Thirty patients with severe bacterial infections were treated with 50 mg of cefodizime per kg of body weight once daily or 50 mg of ceftriaxone per kg once daily for 10 ؎ 3 days. The effect of cefodizime and ceftriaxone on the phagocytic capacity and generation of reactive oxygen intermediates after phagocytosis by granulocytes was assessed prior to, during, and after therapy. Flow cytometry was used to study phagocytic capacity by measuring the uptake of fluorescein-labeled bacteria. The generation of reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Ethical (and economic) problems, the good "classical" antibacterial activity of this drug, and the unclarified mechanism of action and cellular targets have made it difficult to establish satisfactory protocols to illustrate the advantages of such an IRM antibiotic. In the study by Wenisch et al (410), phagocyte function recovered significantly earlier in a group of 15 infected patients receiving cefodizime than in a comparable group treated with ceftriaxone, but the only apparent clinical advantage was earlier defervescence in the cefodizime-treated group. No reports are available on the consequences of prophylactic administration of cefodizime in patients at risk of infections.…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical (and economic) problems, the good "classical" antibacterial activity of this drug, and the unclarified mechanism of action and cellular targets have made it difficult to establish satisfactory protocols to illustrate the advantages of such an IRM antibiotic. In the study by Wenisch et al (410), phagocyte function recovered significantly earlier in a group of 15 infected patients receiving cefodizime than in a comparable group treated with ceftriaxone, but the only apparent clinical advantage was earlier defervescence in the cefodizime-treated group. No reports are available on the consequences of prophylactic administration of cefodizime in patients at risk of infections.…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%
“…Restoration of phagocytic microbicidal function could lead to accelerated clinical improvement or better coverage of potential superinfections. Cefodizime, a broad-spectrum cephalosporin, has been proposed as such a biological response modifier antibiotic (195,324,410). It is even possible that quinolones may be active in immunocompromised individuals not only through their bactericidal potency but also through immunoenhancing effects (57,85).…”
Section: Immunocompromised Individualsmentioning
confidence: 99%
“…The oxidative burst can be altered, enhanced, or decreased by a number of substances and medical drugs such as antibiotics [36,54,55], nitric oxide [14], amphotericin B, lipid emulsions [29], and anesthetics [12,17]. It has been found that the oxidative burst is impaired during sepsis [13,32,47,53].…”
Section: Introductionmentioning
confidence: 98%
“…In studies that used FACS to evaluate the effects of antimicrobial treatments on neutrophilic burst oxidative activity and phagocytosis (Wenisch et al, 1995;Wenisch et al, 1996), no changes in ROS production were observed in patients who used clarithromycin. In a different study, an increase in neutrophilic oxidative burst activity was observed (Shirai et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have investigated the role of these two drugs over the modulation of inflammatory responses, including the production of reactive oxygen species (ROS) by phagocytes (Umeki, 1993;Lemke, 1995;Shirai et al, 1995;Wenisch et al, 1995;Wenisch et al, 1996;Abdelghaffar et al, 1997;Kadota et al, 1998;Kadir et al, 2000;Abdelghaffar et al, 2002;Jain et al, 2002;Sugihara et al, 2003;Tamaoki et al, 2004;Ishida et al, 2007;Yano et al, 2011), none have evaluated the effects of co-administration of the two drugs.…”
Section: Introductionmentioning
confidence: 99%